New familial cases of karyomegalic interstitial nephritis with mutations in the FAN1 gene - Imen Rejeb; Mouna Jerbi; Houweyda Jilani; Hanène Gaied; Yasmina Elaribi; Syrine Hizem; Raja Aoudia; Hafedh Hedri; Chiraz Zaied; Salwa Abid; Hassen Bacha; Taieb BenAbdallah; et al. (BMC, 2021)
Abstract Background Karyomegalic interstitial nephritis (KIN) is a rare disease entity first described by Burry in 1974. The term KIN was introduced by Mihatsch et al. in 1979. KIN is characterized by chronic tubulointerstitial nephritis associated with enlarged tubular epithelial cell nuclei, which leads to a progressive decline of renal function. The prevalence of this disease is less than 1% of all biopsies, and its pathogenesis is unclear. KIN results from mutations in FAN1 (FANCD2/FANCI-Associated Nuclease 1), a gene involved in the DNA damage response pathway, particularly in the kidney. In this study, we report two Tunisian consanguineous families with KIN caused by mutations in the FAN1 gene. Methods Direct sequencing of the coding regions and flanking intronic sequences of the FAN1 gene was performed in three affected members. Three prediction programs (Polyphen-2 software, SIFT, and MutationTaster) were used to predict the functional effect of the detected variations. Results Two causative frameshift variants in the FAN1 gene were identified in each family: The previously described frameshift mutation c.2616delA (p.Asp873ThrfsTer17) and a novel mutation c.2603delT (p.Leu868ArgfsTer22) classified as "pathogenic" according to the American College of Medical Genetics and Genomics (ACMG) guidelines. Conclusion To our best knowledge, this is the first Tunisian study involving familial cases of KIN with mutations in the FAN1 gene. We hypothesize that these findings can expand the mutational spectrum of KIN and provide valuable information on the genetic cause of KIN.